Quantitative Diffusion-Weighted MR Imaging in Transient Ischemic Attacks - Kamal, Ayeesha K. (AJNR Am J Neuroradiol, 2002)
BACKGROUND AND PURPOSE: The risk of stroke after a transient ischemic attack (TIA) is high. Appropriately directed therapies may reduce this risk. However, sensitive means of detecting the presence of subtle neuronal ischemia are lacking. We investigated the potential use of quantitative diffusion-weighted (DW) MR imaging in the detection of deficits produced by transient cerebral ischemia. METHODS: Twenty-eight patients who came to the stroke service from the emergency room of a tertiary teaching hospital with the final diagnosis of transient cerebral ischemia underwent conventional MR imaging, MR angiography, and DW MR imaging within 24 hours of presentation. Fifteen patients had normal conventional DW images confirmed by a staff neuroradiologist and neurologist. For these patients, absolute quantitative diffusion values were subsequently calculated for the clinically relevant brain region and were compared with the values calculated for the corresponding contralateral unaffected brain region. Thirteen patients had conventional DW images positive for lesions and were not studied. RESULTS: Quantitative DW imaging enabled detection of abnormal decreases (9–26%, P < .05) in the diffusion constant in brain regions suspected to be clinically involved by ischemia, when compared with the contralateral clinically unaffected brain tissue as well as with two other internal controls. CONCLUSION: Quantitative DW imaging depicts diffusion deficit in patients with TIA. Quantitative DW imaging may have better sensitivity compared with conventional DW imaging in detecting transient cerebral ischemia.